Biotinidase Deficiency and Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The clinical features of 78 symptomatic children with biotinidase deficiency were reviewed and the response to antiepileptic drugs and biotin therapy in 43 (55%) with seizures are reported from the Medical College of Virginia, Richmond, VA.